The Importance of Interagency Collaboration for Crossover Youth: A Research Note. (October 2017) - Wright, Emily M.; Spohn, Ryan; Chenane, Joselyne; Juliano, Nick
Crossover or dually involved youth are youth enmeshed in the child welfare system (CWS) and juvenile justice system (JJS). Given their dual status and high needs, attention has recently focused on how to best respond to them in an integrated, interagency fashion. The Crossover Youth Practice Model (CYPM) is designed to facilitate interagency collaboration between the CWS and JJS in order to enhance services and diversion to these youths. This study reports on the benefits and challenges that the JJS and CWS, as well as the personnel working within them, experience by participating in a CYPM effort in a Midwestern county, and provides recommendations for continued improvements in interagency collaborations for crossover youth.